Plasmodium knowlesi in humans, macaques and mosquitoes in peninsular Malaysia - Vythilingam, I.; NoorAzian, Y.M.; Huat, T.C.; Jiram, A.I.; Yusri, Y.M.; Azahari, A.H.; NorParina, I.; NoorRain, A.; LokmanHakim, S. (BMC, 2008)
Background Since a large focus of human infection with Plasmodium knowlesi , a simian malaria parasite naturally found in long-tailed and pig tailed macaques, was reported in Sarawak, Malaysian Borneo, it was pertinent to study the situation in peninsular Malaysia. A study was thus initiated to screen human cases of Plasmodium malariae using molecular techniques, to determine the presence of P. knowlesi in non- human primates and to elucidate its vectors. Methods Nested polymerase chain reaction (PCR) was used to identify all Plasmodium species present in the human blood samples sent to the Parasitology laboratory of Institute for Medical Research. At the same time, non-human primates were also screened for malaria parasites and nested PCR was carried out to determine the presence of P. knowlesi . Mosquitoes were collected from Pahang by human landing collection and monkey-baited-traps situated on three different levels. All mosquitoes were identified and salivary glands and midguts of anopheline mosquitoes were dissected to determine the presence of malaria parasites and nested PCR was carried out on positive glands. Sequencing of the csp genes were carried on P. knowlesi samples from humans, monkeys and mosquitoes, positive by PCR. Results and Discussion Plasmodium knowlesi was detected in 77 (69.37) of the 111 human samples, 10 (6.90) of the 145 monkey blood and in 2 (1.7) Anopheles cracens . Sequence of the csp gene clustered with other P. knowlesi isolates. Conclusion Human infection with Plasmodium knowlesi is occurring in most states of peninsular Malaysia. An. cracens is the main vector. Economic exploitation of the forest is perhaps bringing monkeys, mosquitoes and humans into increased contact. A single bite from a mosquito infected with P. knowlesi is sufficient to introduce the parasite to humans. Thus, this zoonotic transmission has to be considered in the future planning of malaria control.